PHYTOCHEMICAL, ANTIOXIDANT AND ANTIMICROBIAL STUDIES OF THE CRUDE EXTRACT OF Curvulariasp. ISOLATED FROM THE LEAVES OF THE MEDICINAL PLANT Piliostigma thonningii (Fabaceae) (FUDMA JOURNAL OF SCIENCES, 2021)
Recently, there is biotechnological interest in secondary metabolites of endophytes since they have been shown to be capable of producing substances of pharmacological importance. Piliostigmathonningii is a tree whose parts are widely employed in Nigeria for diverse medicinal applications. The aim of this study is to investigate the phytochemical composition, the antiradical and in vitro antimicrobial potentials of the crude ethyl acetate extract of Curvularia sp isolated from the leaves of the plant. The endophytic fungus was isolated, purified, and identified using conventional methods. While standard procedures was employed in the determination of the phytochemical constituents, quantitative estimation of the total phenol and flavonoid were done by spectrophotometric method using gallic acid and quercetin as standards respectively. While the antioxidant activity was determined by DPPH scavenging assay, the agar well diffusion method was employed to screen for its antimicrobial capabilities. Results showed the presence ofimportant phytoconstituents notably alkaloid, flavonoid, phenolics, tannin, saponins among others. While the antioxidant assay showed the total phenolic and flavonoid contents to be 212.55 ± 1.2 mgGAE/g extract and 143.16 ± 0.8 mgQE/g extract respectively, a 74.45 ± 0.11% free radical scavenging activity was observed compared to ascorbic acid standard that exhibited a 87.92 ± 0.17% inhibition. At the highest investigated concentration of 1 mg/mL, the extract produced antibacterial activity only against Escherichia coliandPseudomonas aeruginosa. The results showed that the extract exhibits marked antioxidant and selected antibacterial effects thus justifying the assertion that endophytic bioactive compounds have promising applications in the field of medicine.
Keywords: Antioxidant, Antimicrobial, Curvulariasp, Phytochemical, Secondary Metabolites